Gp120 modulates the biology of human hepatic stellate cells: a link between HIV infection and liver fibrogenesis. Issue 4 (7th September 2009) - Bruno, Raffaele; Galastri, Sara; Sacchi, Paolo; Cima, Serena; Caligiuri, Alessandra; DeFranco, Raffaella; Milani, Stefano; Gessani, Sandra; Fantuzzi, Laura; Liotta, Francesco; Frosali, Francesca; Antonucci, Giorgio; et al.
Abstract : Objective: In patients with hepatitis C virus (HCV)/HIV co-infection, a faster progression of liver fibrosis to cirrhosis has been reported. In this study, an investigation was carried out to determine whether gp120, an HIV envelope protein, modulates the biology of human hepatic stellate cells (HSCs), key cell types in the pathogenesis of fibrosis. Methods: Myofibroblastic HSCs were isolated from normal human liver tissue. Gene expression was measured by real-time PCR. Cell migration was assessed in Boyden chambers. Intracellular signalling pathways were evaluated using phosphorylation-specific antibodies or by transfection of a reporter plasmid. Results: Transcripts for the chemokine receptors CCR5 and CXCR4, which bind gp120, were detectable in human HSCs. Upon exposure to M-tropic recombinant gp120, which binds CCR5, a significant increase in HSC chemotaxis was observed (1.6±0.3-fold, p=0.03). The effects of gp120 were prevented by protein inactivation. gp120 also resulted in a significant increase in secretion (1.5±0.3-fold, p=0.03) and gene expression (1.47±0.13-fold, p=0.02) of the proinflammatory chemokine monocyte chemoattractant protein-1, and in increased gene expression of tissue inhibitor of metalloprotease-1 and interleukin-6 (2.03±0.57-fold, p=0.02). gp120-induced migration required Akt activation. gp120 also induced activation of nuclear factor-κB (NF-κB) and p38 MAPK . Preincubation of HSCs with TAK779, a CCR5 receptor antagonist, prevented gp120-mediated chemotaxis and monocyte chemoattractant protein-1 secretion. Expression of CCR5 was detectable in areas of inflammation and fibrogenesis in liver biopsies of patients with HCV/HIV co-infection. Conclusions: This study shows that HIV gp120 modulates different aspects of HSC biology, including directional cell movement and expression of proinflammatory cytokines. These results identify a direct pathway possibly linking HIV infection with liver fibrogenesis via envelope proteins.